A Relationship between Sexual Communication and Self-esteem on Sexual Satisfaction in Early Adult Married Women - Kongsri, Suranrat (Journal of Health Science of Thailand, 2018)
The purpose of this research was to study a relationship between sexual communication and self - esteem on sexual satisfaction in early adult married women. Research participants were 99 women aged 25 - 35 years, who have been married 2 to 4 years and had a minimum education of 2- year-college. The participants were divided into 4 groups according to their self - esteem and sexual communication levels. The instruments were Self - esteem Inventory (Coopersmith, 1981), Sexual Communication Inventory, and Sexual Satisfaction Inventory (Hudson, 1990). A two-way analysis of variance was utilized for statistical analysis. The result indicates that the married women with a high level of sexual communication reported significantly greater sexual satisfaction than those with a low level of sexual communication (p<0.01). However, neither self - esteem nor an interaction between self - esteem and sexual communication has any effect on sexual satisfaction.